Comparison of world views related to attitude towards modern biotechnology across religion and races - Latifah Amin; Jamaluddin Md. Jahi; Abdul Rahim Md. Nor; Mohamad Osman; Nor Muhammad Mahadi (Universiti Kebangsaan Malaysia, 2006)
Modern biotechnology has been classified as a complex emerging issue that exhibits high salience combined with limited knowledge on part of the public. It has been suggested by social scientists that any complex object may be located in a variety of general classes where its evaluation may be strongly affected by extraneous concerns. From the perspectives of several earlier researchers, attitudes towards biotechnology would be expected to follow from the more general class of attitudes to which they pertain, also termed as worldviews. These worldviews include general biotechnology promise and concern, societal values ,impact of technology, confidence on key actors, and religious attachment. Demographic characteristics have been known to affect many attitudes and values. The purpose of this paper is to compare these worldviews across religion and races. A survey was carried out on 1017 respondents from various interest groups in the Klang Valley region. Results of the survey have shown that there were differences in general biotechnology promise, confidence on key actors, impact of technology, societal values and religious attachment across religion and races while general biotechnology concerns only differed across races but not religion